Pengembangan Instrumen Penilaian Sikap Disiplin Belajar Peserta Didik Kelas X Madrasah Aliyah - Sapti Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2021)
In the implementation of the 2013 Curriculum, attitude competence is one of the main components of learning, but there are not many quality measurement attitude competency instruments. The purpose of this study was to obtain quality disciplinary attitude assessment instruments for class X students. This type of research is research and development using the Borg & Gall model. The stages of the activities carried out are the identification of potentials and problems; Gathering Information; Model Development; Model Validation; Model Revision; Model Trials; Model Revision; Wider Trial; and Final Model Revision. Based on the results of the research and discussion in this study, it can be concluded that there is no difference in the learning discipline of students between those who live with their parents and students who live in the dormitories. This is because students are adults and can be independent, and already have responsibilities even though they are not with their parents. The results of the calculation of the average score of learning discipline of class X students at MAN 3 in the 2016/2017 academic year Bantul is 96.2466 and is included in the high category.